The Use of Fibrin Sealants in Reducing Postoperative Complications in Skull Base Surgery: A Systematic Review and Meta-Analysis - Eberly, Hänel W.; Rosi-Schumacher, Mattie; Sciscent, Bao Y.; Truong, Nguyen; King, Tonya S.; Goldenberg, David; Goyal, Neerav (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objective To determine if using fibrin sealants (FS) during skull base (SB) surgery reduces complications.Methods PubMed, Cochrane, Web of Science, and Embase databases were searched for studies of patients who underwent SB surgery with use of an FS. A systematic review was conducted according to PRISMA guidelines. Primary outcomes included incidence of cerebrospinal fluid (CSF) leak, revision surgery, infection, and drain placement. Methods for meta-analysis were performed including tests of homogeneity and both fixed-effects and random-effects models.Results A total of 30 articles met the inclusion criteria. There were 3,681 patients, including 2,220 patients who received FS and 1,461 patients who did not. The most common surgical approaches were posterior fossa (27.4%) and transsphenoidal (18.2%). The FS group was less likely to have a lumbar drain placed (1.7% versus 8.1% of the control group). The difference in drain placement incidence between groups for the studies which included both groups was −0.135 (95% CI [−0.285, 0.016], p = 0.079) for the random-effects model and −0.038 (95% CI [−0.068, −0.008], p = 0.014) for the fixed-effects model. The incidence of CSF leak was 11.3% in the control group and 6.8% in the FS group. The rate of infection was higher in the control group (6.1%) compared with the FS group (3.3%), although not statistically significant. The rate of revision surgery was similar between the two groups (3.0% in the control group versus 2.4% in the FS group).Conclusion Patients who underwent SB surgery with FS may have lower incidences of drain placement than patients whose surgery did not involve FS.
Keywords: skull base; fibrin sealants; cerebrospinal fluid leak; lumbar drainage